GLOBAL INSTITUTIONAL CHANGE IN LATE TWENTIETH CENTURY: CONNECTIONS BETWEEN LATIN AMERICA AND CENTRAL EUROPE - Riojas López, Carlos (2016)
The paper has as objective to explore how the different processes of institutional change in Latin America and Central Europe were entangled in a context of global transformations. To support my argument, I offer a comparison of the Human Development and Education Index in order to explore a possible relationship between these variables and the advances on the processes of democratization in Latin America and Central Europe. Some neo-institutional economic theorists mentioned that education level has the potential to impact the speed of institutional change; however, based in empirical evidences I argue that education’s variable explains part of the process but not all phenomenon as a whole.